Comparative study of mepiquat chloride and chlormequat chloride application in cotton - Lamas, Fernando Mendes (Pesquisa Agropecuaria Brasileira, 2001)
This work was carried out to compare the effects of the growth regulators mepiquat chloride and chlormequat chloride applied in combination or separately in the cotton (Gossypium hirsutum L.) cultivar CNPA ITA 90. The experiment was evaluated in Mato Grosso State, Brazil, in the agricultural year of 1998/99. Fifteen treatments were studied with four replications, using randomized complete block design. The height of the plants with the parceled application was 24% smaller in relation to the control treatment, independently on the chemical. The boll weight was greater with the application of growth regulator, not depending on the product and the application outline. The weight of 100 seeds depends on the application sequence and on the chemical; it was larger when the first two applications were with chlormequat chloride. There was not significant effect of the growth regulators in the fiber percentage; however, the fiber productivity was influenced by the product and by the application outline; with three or two applications of the same product, the largest productivity was obtained with mepiquat chloride.